Accounting Practices and Financial Accountability in Tourism-Based Small and Medium Enterprises in Bali - Sotarduga Napitupulu; Devy Mawarnie Puspitasari (Journal of Management, 2026)
Tourism-based small and medium enterprises (SMEs) play an important role in supporting local economic development in Bali. However, many SMEs still face challenges in implementing proper accounting practices and maintaining financial accountability. This study aims to examine accounting practices and financial accountability in tourism-based SMEs in Bali. The research employs a qualitative approach using interviews, observations, and document analysis to understand how SME owners manage their financial records and financial reporting activities. The findings indicate that most tourism SMEs in Bali still rely on simple bookkeeping practices, primarily focusing on recording daily income and operational expenses. While these practices help business owners monitor financial activities, many SMEs have not yet implemented standardized accounting systems or prepared structured financial statements. Limited accounting knowledge, lack of financial literacy, and insufficient training are identified as major factors influencing the quality of financial reporting among SMEs.Despite these challenges, some tourism SMEs have begun adopting digital accounting tools and simplified financial reporting standards such as SAK EMKM to improve financial management and transparency. The study suggests that strengthening financial literacy, promoting accounting training programs, and encouraging the adoption of digital financial tools can improve financial accountability among tourism-based SMEs. Improving accounting practices will not only enhance business sustainability but also support the development of a more resilient tourism economy in Bali.